Current Problems of Personnel Training for the Tourism Sector in Uzbekistan - Nargis Nuriddinovna Mukumova (Indonesian Journal of Law and Economics Review, 2020)
The article considers issues relating to existing system of personnel training for the tourism sector. In connection with the active development of this sector of the economy has appeared the need for clear interaction between the system of professional education and the labor market. Despite the fact that a large number of special educational institutions and higher educational institutions train personnel for the tourism industry, there is a shortage of qualified personnel in the tourist job market. According to experts, today the majority (up to 75%) of employees of tourism companies do not have education of a specialist in the field of tourism. Currently, the market situation is such that graduates of specialized educational institutions do not meet professional requirements that meet international standards. Today's specialists have a low professional level, so hotels and travel agencies that have their own specialist training programs have to re-train the hired employees. Training and retraining of personnel in the field of tourism can become one of the main advantages of the organization, as the quality of the services provided depends on the qualifications of the personnel, and the satisfaction of guests in the service sector is achieved by the competence of the personnel. The purpose of improving the professional training of personnel for the tourism industry is to create a sustainable development of the system of professional training that would meet the needs and development of the individual, the state and society as a whole, which would improve the quality of professional training of specialists in the field of tourism.